Associations between primary care practice type and patient-reported access - K Selby; J-C Zuchuat; C Cohidon; N Senn (BMC, 2018)
Abstract Background We recently defined a global typology of primary care (PC) in Switzerland using a mixed inductive/deductive approach to construct latent, composite variables that summarize variance between practices. Now we explore associations between the primary variable that describes the comprehensiveness of services and patient-perceived access to PC in Switzerland. Methods Cross-sectional surveys were administered to physicians from the Swiss PC Active Monitoring (SPAM) network and their patients. The primary outcomes were patient responses to: "Was it easy to get the appointment?", "The opening hours are too restricted" and "In the past 12 months, did you postpone or abstain from a visit to this doctor or another GP when you needed one?" Multivariate, multilevel analyses with stepwise regression were used to assess associations between practice type (practices with a broader range of services have higher scores) and perceived access, controlling for patient characteristics. Results One hundred and ninety nine of 200 PC physicians in the network completed the questionnaire. Of 2628 patients approached after a physician visit, 1791 accepted (participation = 76%), with 9 patients at each practice. No association was observed between comprehensiveness of services and difficulty getting an appointment. When controlling for patient factors, there was a weak association between higher scores for comprehensiveness of services and patients reporting that the opening hours are too restricted (p = 0.05), though this was no longer significant after controlling for language area. Greater comprehensiveness of services was associated with fewer patients needing to postpone visits (OR 0.93, 95%CI 0.88-0.99, p = 0.03). Conclusions Though fewer patients report needing to postpone visits at practices with more comprehensive offering of services, there is limited evidence of associations between patient-reported access and a global typology of Swiss primary care.